2021
DOI: 10.1007/s00253-021-11726-9
|View full text |Cite
|
Sign up to set email alerts
|

TonB-dependent receptor epitopes expressed in M. bovis BCG induced significant protection in the hamster model of leptospirosis

Abstract: Leptospirosis is an emerging infectious disease caused by pathogenic Leptospira spp. A universal vaccine against leptospirosis is likely to require highly conserved epitopes from pathogenic leptospires that are exposed on the bacterial surface and that generate a protective and sterilizing immune response. Our group recently identified several genes predicted to encode TonB-dependent receptors (TBDR) in Leptospira interrogans using a reverse vaccinology app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Some other Leptospira spp. chimeric constructions have been designed and explored for vaccine [34][35][36][37], but their potential as a diagnostic marker has not been explored yet. Other published dry lab studies explored possible new chimeric construction by using a combination of epitope prediction and molecular docking for vaccine and/or diagnostic goals [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Some other Leptospira spp. chimeric constructions have been designed and explored for vaccine [34][35][36][37], but their potential as a diagnostic marker has not been explored yet. Other published dry lab studies explored possible new chimeric construction by using a combination of epitope prediction and molecular docking for vaccine and/or diagnostic goals [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Dorneles et al (2020) [ 51 ] investigated the same antigens used in different chimeric constructs to transform BCG. Recently, Bettin et al (2022) [ 52 ] developed an rBCG vectored vaccine expressing a chimeric antigen based on the TonB-dependent receptor (TBDR) epitopes (LIC10896, LIC10964, and LIC12374) from L. interrogans . Hamsters vaccinated with the rBCG:TBDRchi construct were fully protected from lethal leptospirosis, whereas the same recombinant protein as a subunit vaccine failed to protect animals (44.4% survival, p > 0.05; data not published).…”
Section: Live Recombinant Antigen Delivery Vehiclesmentioning
confidence: 99%
“…Hamsters vaccinated with the rBCG:TBDRchi construct were fully protected from lethal leptospirosis, whereas the same recombinant protein as a subunit vaccine failed to protect animals (44.4% survival, p > 0.05; data not published). In studies performed by Oliveira et al (2019) [ 50 ], Dorneles et al (2020) [ 51 ], and Bettin et al (2022) [ 52 ], it was shown that rBCG constructs were able to induce immune protection and prevent renal colonization against challenge with virulent L. interrogans . The combination of rBCG and chimeric multiepitope proteins appears to be a promising alternative against leptospirosis [ 53 ].…”
Section: Live Recombinant Antigen Delivery Vehiclesmentioning
confidence: 99%
“…TonB-dependent receptors (TBDRs) are outer membrane proteins found in many Gram-negative bacteria that play a key role in the uptake of essential nutrients, such as iron and vitamin B12, from the host environment ( Blanvillain et al, 2007 ; Moynié et al, 2017 ). TBDRs are highly conserved among bacteria and are essential for bacterial survival and growth, making them attractive targets for the development of vaccines ( Grassmann et al, 2017 ; Bettin et al, 2022 ). One advantage of targeting TBDRs is that they are expressed on the outer surface of the bacterial cell, making them accessible to antibodies and other immune system components.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a vaccine based on the TBDR of the pathogenic bacterium Haemophilus influenzae was shown to be highly effective in preventing infection in a mouse model ( Webb and Cripps, 1999 ). Other studies have focused on the development of vaccines targeting TBDRs in pathogenic bacteria such as Aeromonas hydrophila ( Abdelhamed et al, 2017 ) , Mycobacterium bovis ( Bettin et al, 2022 ), Pseudomonas fluorescens ( Hu et al, 2012 ), and Acinetobacter baumannii ( Yang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%